ATRIBUT YANG MENJADI PERTIMBANGAN NASABAH DALAM MEMILIH BANK (Studi Kasus PT Bank Rakyat Indonesia Cabang Jambi) - Azizah Azizah (Universitas Batanghari Jambi, 2011)
This study uses primary data and secondary data and the number taken in a representative sample using purposive random sampling method. Analysis tool to analyze this research uses chochran test. From the results of discussion by using the test results obtained chochran of Testing Decision I: Reject Ho because the Q count (46.4)> Q tab (16.92). So there is no common opinion of respondents about the attributes. Thus, the need to be tested II by removing attributes that have the smallest proportion of YES answers, is an attribute